Assessing the Impact of Pro-Poor Tourism Development on Poverty Alleviation in Imo State, Nigeria - Nnajieto, Charles Chibuzor; Nnajieto, Augustina Onyedikachi (Asian Journal of Science, Technology, Engineering, and Art, 2025)
This study assessed the impact of pro-poor tourism development on poverty alleviation in Imo State, Nigeria. Employing a descriptive survey research design, the study focused on a population of 391 staff members from the Ministry of Tourism in Imo State. Using a census sampling technique, the entire population was studied to ensure comprehensive coverage. Data were collected through a structured instrument titled the Pro-Poor Tourism Development and Poverty Alleviation Questionnaire (PPTDPAQ), which was validated by three subject-matter experts to ensure content relevance and reliability. The collected data were analyzed using mean and standard deviation to determine trends and patterns. The findings revealed that tourism development initiatives in Imo State are significantly aligned with pro-poor tourism principles, promoting local employment, enterprise support, and community participation. Moreover, the study established that such initiatives have contributed meaningfully to poverty alleviation among local populations by creating economic opportunities and improving livelihood conditions. Based on the findings, the study recommended that the government implement skill acquisition programmes tailored to tourism-related jobs, thereby enhancing local capacity. Furthermore, it emphasized the need for transparent and equitable distribution of tourism revenues to ensure inclusive and sustainable poverty reduction outcomes.